Atraumatic spontaneous swelling of sternoclavicular joint: a case report - Kottasseri, Nazia E.; Kalathingal, Mohammed A.; Veettil, Shajitha T. (International Journal of Research in Medical Sciences, 2020)
Atraumatic spontaneous swelling of the Sternoclavicular Joint (SCJ) is not very common in elderly women. The SCJ is an integral part of the shoulder girdle that connects the upper limb to the axial skeleton. Trauma, degeneration, infections and other disease processes that affect synovial joints are the common causes of swelling of the SCJ. Here authors report a case of nontraumatic spontaneous anterior subluxation of the sternoclavicular joint in 66-year-old women without any underlying pathology who presented with sudden onset of a nontender swelling in the suprasternal area. The patient was treated conservatively and remained asymptomatic throughout 6 months follow up.